1996
DOI: 10.1086/178002
|View full text |Cite
|
Sign up to set email alerts
|

Optical Continuum and Emission‐Line Variability of the Seyfert 1 Galaxy Markarian 509

Abstract: We report on the results of a 5 year coordinated program of spectroscopic monitoring of the luminous Seyfert 1 galaxy Markarian 509. The Hb and He II j4686 emission lines are found to respond to continuum variations with time lags of D80 and D60 days, respectively, considerably longer than the emission-line lags measured for other Seyfert galaxies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 7 publications
2
25
0
1
Order By: Relevance
“…2). This is consistent with the results of the monitoring program of Mrk 509 by Carone et al (1996) who found the Hβ λ4861 and He ii λ4686 emission lines to respond to continuum variations with time lags of about 80 and 60 days respectively, considerably longer than the emission line lags measured for other Seyfert galaxies and also longer than the duration of the XMM-Newton campaign. Finally, we proceeded to correct the OM and UVOT filter data (described in Sect.…”
Section: Correction For Emission From the Broad Line Region (Blr) Andsupporting
confidence: 91%
“…2). This is consistent with the results of the monitoring program of Mrk 509 by Carone et al (1996) who found the Hβ λ4861 and He ii λ4686 emission lines to respond to continuum variations with time lags of about 80 and 60 days respectively, considerably longer than the emission line lags measured for other Seyfert galaxies and also longer than the duration of the XMM-Newton campaign. Finally, we proceeded to correct the OM and UVOT filter data (described in Sect.…”
Section: Correction For Emission From the Broad Line Region (Blr) Andsupporting
confidence: 91%
“…This method is not exactly the same as usually used; the usually used interpolation method only interpolates one lightcurve and the other lightcurve is paired with this interpolated lightcurve [1] . However, our method gives nearly the same CCF as Carone et al (2006) [7] , who obtained a lag of about 80 days, within the uncertainty region of our result. The uncertainty for each centroid is obtained as described in Peterson et al (1998) [8] .…”
Section: Mrk 509supporting
confidence: 89%
“…We acquire about five years' data of Mrk 509 from AGN watch website; they are the data used in Carone et al (1996) [7] . All of their 151 Hβ spectra are decomposed as described in the last section.…”
Section: Mrk 509mentioning
confidence: 99%
“…This broad-emission-line gas is emitted within 0.1 pc of the central black hole (Peterson & Wandel 2000). In Mrk 509, the size of the broad line region (BLR) determined from Hβ measurements is 80 light-days (0.067 pc) (Carone et al 1996). The absorbing gas is probably located at a somewhat larger distance, although both aspects of the AGN phenomenon are likely to have similar abundances because of their close origin.…”
Section: Rgsmentioning
confidence: 99%